Talent identification and development: An academic review (University of Edinburgh, 2007)
1. An Introduction to Detecting and Identifying Talent 1.1 Natural versus scientific selection 1.2 The Nature View - Arguments for and against 1.3 Summary, and Overview of the Review 2. Research Implications for Talent Detection and Identification Models 2.1 A Review of Relevant Research in Talent Detection and Identification 2.2 NATURE vs NURTURE: Physiological and Anthropometric Correlates of Success 2.2.1 Developmental Considerations 2.2.2 Anthropometrical and Physical Determinants of Performance Vary with Age 2.2.3 Anthropometrical and physical measures are not always consistent performance determinants 2.3 NATURE AND NURTURE: Fundamental Movement Skills 2.4 NURTURE vs NATURE: Psychological Determinants of Excellence 2.5 Summary of Research on Talent Detection and Identification Models 3. Conceptual Models of Talent Detection and Identification 3.1 A Review of Conceptual Models of Talent Detection and Identification 3.2 Implications of a Multiplicative model of talent and individual differences 3.3 Summary 4. Current Practices In Talent Detection and Identification 4.1 Talent Detection and Identification Procedures in Sport 4.1.1 Natural Selection 4.1.2 Anthropometrical and physiological talent identification models 4.1.3 Generic Model 4.2 Non-British Talent Detection and Identification Procedures 4.2.1 Performance Models 4.2.2 Anthropometric Models 4.2.3 Why such success for the Communist nations? 4.2.4 Summary 4.3 Talent Search and Sport Interactive 4.3.1 Empirical basis of Talent Search and Sport Interactive 4.3.2 Performance on basic skills 4.3.3 The Role of Talent Search in the Sporting Success of Australia 5. Talent Detection and Identification Methods in Non-Sport Settings 5.1 Gifted Artists and their Detection/ Identification 5.2 Talent in the World of Dance and Music 5.3 Detection/Identification of Academic Talent 5.4 Summary 6. Addressing the Dichotomy between Empirical Evidence and Practice 6.1 Defining the Dichotomy 6.2 Characterising the 'Hothousing Potential' Environment 6.3 Optimising Environmental Factors to Facilitate Talent Development 6.4 Summary 7. A Theoretical Model of Talent Development - and Best Fits with Practice 7.1 Bloom's Model of Staged Talent Development 7.2 How Valid is Bloom's Model? - Support, Importance & Limitations 7.3 Multiple Developmental Pathways to Excellence 7.4 Existing Applied Models of Talent Development and What is Needed 7.5 Summary 8. Summary of Conclusions and Implications 8.1 Research 8.2 Funding and Direction of Talent Identification Schemes 8.3 Potential Outcomes of Talent Identification and Development Schemes